Role of α-synuclein in adult neurogenesis and neuronal maturation in the dentate gyrus. - Winner, Beate; Regensburger, Martin; Prots, Iryna; Winkler, Jürgen; et al. (Journal of Neuroscience, 2012)
α-Synuclein has been reported to be important in modulating brain plasticity and to be a key protein in neurodegenerative diseases, including Lewy body dementia (LBD). We investigated how α-synuclein levels modulate adult neurogenesis and the development of dendritic arborization and spines in the dentate gyrus, in which new neurons are constantly added. In the human hippocampus, levels of endogenous α-synuclein were increased in LBD, and the numbers of SOX2-positive cells were decreased. We investigated whether newly generated neurons were modulated by endogenous α-synuclein, and we found increased adult neurogenesis in α/β-synuclein knock-out mice. In contrast, overexpression of human wild-type α-synuclein (WTS) decreased the survival and dendritic development of newborn neurons. Endogenous α-synuclein expression levels increased the negative impact of WTS on dendrite development, suggesting a toxic effect of increasing amounts of α-synuclein. To attempt a rescue of the dendritic phenotype, we administered rolipram to activate the cAMP response element-binding protein pathway, which led to a partial rescue of neurite development. The current work provides novel insights into the role of α-synuclein in adult hippocampal neurogenesis.